Nursing Care in Risk of Violent Behavior - Razuli, M Fauzan; Rahayu, Adisty (International Journal Scientific and Professional, 2023)
The aim of this research is to analyze and design nursing care for two patients, who are at risk of violent behavior. Observations, interviews, and medical record documentation studies are data collection methods. Based on the research results, it is known that both patients have a high risk of violent behavior, especially related to a history of previous violence and underlying mental disorders. Initial assessment includes identification of potential triggers for violence, evaluation of level of coping, and assessment of social support. Risk of violent behavior is the patient's second nursing diagnosis. Treatment plans are implemented with a focus on violence prevention, involving collaboration with a multidisciplinary team, including medical personnel, and psychiatrists. Nursing interventions involve therapeutic approaches to improve coping, interpersonal skills training, and close monitoring for signs of violence. Periodic evaluations are conducted to assess the effectiveness of the treatment plan and identify changes in patient behavior. Discharge planning involves coordination with family and mental health services in the community to ensure continuity of care after discharge. The conclusion of this research is that nursing care for patients at risk of violent behavior requires a careful, proactive and collaborative approach. Implementing integrated violence prevention strategies and close monitoring can help reduce the risk of violent incidents.